DUA DASA WARSA KEMANDIRIAN BERAS JAWA TENGAH - Sarjana Sarjana; lndrie Ambarsari; Agus H ermawan; Seno Basuki (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2007)
Rice is a strategic commodity on national food security system. Considering the on decreasing of national and world rice stock, the significance of giving much emphasis on rice reliability is increasingly apparent. This article describes the trend of Central Java rice production capacity and selfreliance. This analysis is based on statistics from BPS-Statistics of Jawa Tengah Province. For the last two decades, Central Java has been enhancing the rice self-reliance for the population. However, as the growth rate of rice productions is less than the growth rate of population, so trend of rice available per capita is decreasing. Harvested area and yield rate in some lowland rice areas is going on decrease. By sides, the total annual production and yield can not been continuously increased. Land conversion, water stress requirement, soil sickness, and infestation of pests and diseases are critical factors on increasing the rice production capacity. Intensification quality improvement program, extensive upland rice area, eliminate loses that caused by flood, drought, pests and diseases are strategic options. Social economic and institutional innovation, capital formation, and infrastructures should significantly support such scheme. To keep on those efforts, it is necessary to characterize the existing paddy area and the paddy potential zone based on production performance, its obstacles and problems. The characterization results could be a policy direction on determines the selective innovation, production factor, capital formation, and infrastructure needs.